Era 4.0 Curriculum Development Design - Andri Yuliandi; Desmiarni; Nizwardi Jalinus (AKADEMI TEKNIK ADI KARYA, 2024)
In facing the era of the Fourth Industrial Revolution, curriculum development design becomes crucial to ensure relevant and competitive education. This journal explores the concepts, strategies, and challenges in designing a curriculum that integrates the learning needs of the digital era. The primary focus is on incorporating advanced technologies, such as the Internet of Things (IoT), to ensure learners have a profound understanding of these concepts and can apply them in real-world contexts. This research is a literature review, concluding that the design of 4.0 era curriculum development must be proactive, innovative, and centered on developing competencies that encompass both technical and non-technical aspects. Consequently, education can make a significant contribution to shaping individuals who are ready to compete and adapt in the ongoing digital transformation era